Impulsive and Self-Regulatory Processes in Risky Driving Among Young People: A Dual Process Model - Lazuras, Lambros; Rowe, Richard; Poulter, Damian R.; Powell, Philip A.; Ypsilanti, Antonia (Frontiers in Psychology, 2019)
The present study empirically examined a novel dual process model of self-reported aberrant driving behaviour in young and novice drivers that incorporates both impulsive and self-regulatory processes. Four hundred and nine participants aged 18-25 years (M age = 21.18 years, SD = 2.12; 65.5% females) completed online questionnaires on impulsivity, normlessness, sensation seeking, emotion and self-regulation, and attitudes towards driving safety. Path analysis showed that motor impulsivity was associated with self-reported driving violations, errors, and lapses, whereas sensation seeking was uniquely directly associated with self-reported errors. Non-planning impulsivity, normlessness and sensation seeking had significant indirect effects on self-reported errors, via self-regulation. Finally, motor impulsivity and normlessness had a significant indirect effect on self-reported violations, errors and lapses, via attitudes to driving safety. Based on our findings we suggest that a dual-process approach is relevant to the study of aberrant driving behaviour in young and novice drivers, and the results of the present study have important implications for initiatives to promote driving safety in this population.